Relevansi Ayat-ayat Edukatif dalam Pengembangan Kurikulum Pendidikan Islam di Indonesia - Umiarso Umiarso (Edukasia Islamika, 2018)
The thought of ideal curriculum development in Indonesia keeps on scrolling. It was started from curriculum 1947, 1949, 1952, 1964, 1968, 1975, 1984, 1994, Competence-based Curriculum (KBK), School-based Curriculum (KTSP), and the 2013 Curriculum. Those changes are the answers of global demand to the education quality. However, by looking at the fact that there are many cases of students fight, drug abuse and free sex among students, it can be concluded that the curriculum changes are not in line with the reality in education world. Based on the explanation above, this paper tries to offer an idea to develop curriculum based Qur’an by reviewing one of the term used in Qur’an to refer to the educational process, namely: ‘ta’lim’. Based on the analysis, the word ta’lim has a deep meaning including cognitive, affective, and psychomotor domains. If it is related to the curriculum development, curriculum based Qur’an is a learning model which focuses on the three domains above, as seen on the meaning coverage of ta’lim used in Qur’an.